Social media as a source of political information: First-time voters and the influence of social media on political interest - Ng, Alicia Zi Qin; Jong, Ally Fang Yee; Choong, Wen Yee; Lee, Ming Yi; Nagadarshyini, Maniam (2023)
Social media plays a critical role as a significant source of political information among Malaysians. Generally, youth are categorized as active users of social media in their daily lives. When the government lowered the minimum voting age to 18 years from 21, around 6.23 million Malaysians were first-time voters. However, disinterest in politics occurred among first-time voters. Fifteen interviewees aged 18 to 24 were selected to be the samples in this research to study about the influence of social media on political interest. This research applied Media Dependency Theory (MDT) as the theoretical framework. The contents of social media feed depend on the user’s social networking and social media algorithm, which are able to shape perceptions. Therefore, the political information the first-time voters are exposed to is able to influence the political interest and the decision-making of voting. All the results have been divided into six main themes, which will be linked to the influence of social media on political interest and decision-making on voting. All data collected has been stated to the body of knowledge for future use